Effect of aerobic and load exercises on body fat and lung vital capacity - Rina Yuniana (Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2020)
This study aims to determine how much influence aerobic exercise and weight training have on body fat and vital capacity. This study used an experimental method with a randomized control group pretest-posttest design. The population in this study were 68 female members at the Fitness Center, Faculty of Sport Science, Yogyakarta State University who participated in the weight loss program. The sample in this study was taken purposively by determining the number of members who participated in the training program with the criteria that active members were at least 2 months practicing before the treatment was carried out and women aged 18-25 years. Through these criteria, the sample obtained is as many as 54 people. Of the 54 people, they were divided randomly into three groups, namely the aerobic exercise group of 18 people, the weight training group of 18 people, and the control group of 18 people. The instrument used to measure and collect body fat data used a skinfold caliper, while the vital lung capacity was measured using a spirometer with a Vitalograph brand. The data analysis technique used the normality test, namely the Kolmogorov-Smirnov Test. This test is carried out to determine whether the data has a normal distribution. The homogeneity test used the Levene's Test with the F test. To test the research hypothesis, it was done using Analysis of Variance (ANOVA). This test was conducted to determine the difference in the mean value of the variables between the pretest and posttest in the experimental group. The results of the research analysis showed that aerobic exercise can reduce body fat by 4.651% and increase the vital lung capacity of members at the Fitness Center by 0.2167 liters / BTPS. Weight training can reduce body fat by 2.969%. Weight training can increase the vital capacity of the lungs by 0.1583 liters / BTPS. Aerobic exercise can reduce body fat by 1.68617% higher than weight training. Aerobic exercise can increase the ability of vital lung capacity 0.05833 liters / BTPS higher than weight training. Pengaruh latihan aerobik dan latihan beban terhadap lemak tubuh dan kapasitas vital paru AbstrakPenelitian ini bertujuan untuk mengetahui seberapa besar pengaruh latihan aerobik dan latihan beban terhadap lemak tubuh dan kapasitas vital. Penelitian ini menggunakan metode eksperimen dengan Randomized Control Group Pretest-Posttest Desain. Populasi pada penelitian ini adalah member perempuan di Fitness Center Fakultas Ilmu Keolahragaan Universitas Negeri Yogyakarta yang mengikuti program penurunan berat badan yaitu sebanyak 68 orang. Sampel pada penelitian diambil secara purposive dengan menentukan jumlah member yang mengikuti program latihan dengan kriteria yaitu member aktif minimal 2 bulan berlatih sebelum perlakuan dilaksanakan dan wanita usia 18-25 tahun. Melalui kriteria tersebut maka sampel yang diperoleh yaitu sebanyak 54 orang. Dari 54 orang tersebut dibagi menjadi tiga kelompok secara random, yaitu kelompok latihan aerobik sebanyak 18 orang, kelompok latihan beban sebanyak 18 orang, dan kelompok kontrol sebanyak 18 orang. Instrumen yang digunakan untuk mengukur dan mengumpulkan data lemak tubuh dengan menggunakan skinfold caliper, sedangkan untuk mengukur kemampuan kapasitas vital paru menggunakan spirometer Merk Vitalograph. Teknik analisis data menggunakan uji normalitas yaitu Kolmogorov-Smirnov Test. Uji ini dilakukan untuk mengetahui apakah data mempunyai sebaran yang berdistribusi normal. Uji homogenitas menggunakan uji Levene’s Test dengan uji F. Untuk menguji hipotesis penelitian dilakukan dengan menggunakan Analisis Variansi (ANAVA). Uji ini dilakukan untuk mengetahui perbedaan rerata nilai dari variabel antara pretest dan posttest pada kelompok eksperimen. Hasil analisis penelitian menunjukkan bahwa latihan aerobik dapat menurunkan lemak tubuh sebesar 4,651 % dan meningkatkan kapasitas vital paru pada member di Fitness Center sebesar 0,2167 liter/BTPS. Latihan beban dapat menurunkan lemak tubuh sebesar 2,969 %. Latihan beban dapat meningkatkan kapasitas vital paru sebesar 0,1583 liter/BTPS. Latihan aerobik dapat menurunkan lemak tubuh lebih tinggi 1,68617 % dibanding latihan beban. Latihan aerobik dapat meningkatkan kemampuan kapasitas vital paru lebih tinggi 0,05833 liter/BTPS dibanding latihan beban.